CODE-MIXING IN CINTA LAURA’S VLOG - Ridha Hidayah Fatiqah; Yanuarti Apsari (IKIP Siliwangi, 2022)
Mixing two languages in Indonesia is currently happening. Communities in big cities often combine the use of two languages in life and influence others to do so. This phenomenon can be called code-mixing. The purposes of this study, researchers to analyze the types of code-mixing Cinta Laura’s vlog and to identify the most dominant types of code-mixing. This research used Musyken (2000) theory about code-mixing. The data were taken from Cinta Laura’s vlog updated from Ferbuary until March 2020. The researchers used descriptive qualitative method. There were types of code-mixing, found in Cinta Laura’s Vlog namely insertion, alternation and congruent lexicalization. In addition, the data also showed that insertion is the dominant type of code-mixing that is most found. . Keywords: Factors Motivation, Code-Mixing, Vlog